PEDAGOGICAL AND PSYCHOLOGICAL ROLE OF MUSIC IN CHILDREN'S DEVELOPMENT - Syomkina Adiba Minggirovna (Web of Journals Publishing, 2023)
The article describes the influence of music on humans, its role in the development of children and on their mental performance.
Keywords: competence, musical consciousness, abilities, will, musical skill, music, theater.